An analytical study of undoped symmetric double gate MOSFET (SDG) - Singh, Ajay Kumar (WILEY-BLACKWELL, 2011)
In the present paper, compact analytical models for the threshold voltage, threshold voltage roll-off and subthreshold swing of undoped symmetrical double-gate MOSFET have been developed based on analytical solution of two-dimensional Poisson's equation for potential distribution. The developed models include drain-induced barrier lowering (DIBL) through the V(ds)-dependent parameter. The calculated threshold voltage value, obtained from the proposed model, shows a good agreement with the experimental and published results. The simulation results for potential show that the conduction is highly confined to the surfaces. The threshold voltage sensitivity to the thickness is found to be approximately 0.2%. Model prediction indicates that subthreshold slope is not linearly related to DIBL parameter for thick silicon film. The proposed analytical models not only provide useful insight into behavior of symmetrical DG MOSFETs but also serve as the basis for compact modeling. Copyright (C) 2010 John Wiley & Sons, Ltd.